PLC regulates spontaneous glutamate release triggered by extracellular calcium and readily releasable pool size in neocortical neurons - Feldthouse, Maya G.; Vyleta, Nicholas P.; Smith, Stephen M. (Frontiers in Cellular Neuroscience, 2023)
Dynamic physiological changes in brain extracellular calcium ([Ca2+]o) occur when high levels of neuronal activity lead to substantial Ca2+ entry via ion channels reducing local [Ca2+]o. To study how changes in [Ca2+]o affect neuronal activity, perturbations of the extracellular microenvironment that increase [Ca2+]o are more common, and they decrease intrinsic neuronal excitability and increase evoked and spontaneous synaptic transmission. At excitatory synapses, increased Ca2+ entry, via voltage-activated Ca2+ channels, underlies the increase in evoked release, but not the effect on spontaneous glutamate release. The Ca2+-sensing receptor (CaSR) and other G-protein coupled receptors link [Ca2+]o and spontaneous glutamate release. Phospholipase C (PLC) is activated by G-proteins and is well-positioned to mediate this process. PLC hydrolyzes membrane phosphatidylinositol 4,5-biphosphate, producing IP3 and DAG, two known modulators of synaptic transmission. Patch-clamping neocortical neurons, we confirmed that spontaneous glutamate release substantially increased with [Ca2+]o, and inhibition of PLC activity with U73122 abolished this effect. PLC-β1 is the most abundant isoform in the neocortex, however [Ca2+]o dependent spontaneous release was unchanged in PLC-β1 null mutants (PLC-β1-/-). U73122 completely suppressed this response in PLC- β1-/- neurons, indicating that this residual [Ca2+]o–sensitivity may be mediated by other PLC isoforms. We then tested if vesicles that mediate evoked release were also sensitive to PLC. Using hypertonic sucrose (HS) to probe the vesicles of the readily releasable pool (RRP), we determined that the RRP size was substantially reduced after incubation in U73122, but not U73343. Together these data point to a strong role for PLC in mediating changes in spontaneous release to extracellular cues and in maintaining the RRP.